2020
DOI: 10.3920/jiff2019.0038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red clover-only diets on house crickets (Acheta domesticus) growth and survival

Abstract: This study evaluated the potential of red clover as a sole diet for house crickets (Acheta domesticus, AD) and the effect of ensiling or drying red clover biomass on growth, survival and water consumption of AD. Wild AD were caught near Uppsala, Sweden, and reared in a climate-controlled room under a 12-h light regime. One day-old third-generation cricket nymphs (n=2,880) were used in a 56-day feeding trial. The experimental diets (n=8) were early-cut (pre-bloom) and late-cut (late-bloom) red clover, preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Collavo et al [42] recorded a mean weight of 0.452 g for A. domesticus at the same age when reared on a human refuse diet, whereas Lundy and Parrella [17] recorded considerably lower values in response to food waste diets. Vaga et al [43] reported up to an 80% difference in the weight of A. domesticus fed a control diet containing 19.2% crude protein and 37.6% starch, and a red-clover-based diet. Collavo et al [42] found that an aromatic-arboreal diet is not optimal for A. domesticus, and its unbalanced nutritional value promoted cannibalism.…”
Section: Changes In the Larval Weight In Response To Dietmentioning
confidence: 99%
“…Collavo et al [42] recorded a mean weight of 0.452 g for A. domesticus at the same age when reared on a human refuse diet, whereas Lundy and Parrella [17] recorded considerably lower values in response to food waste diets. Vaga et al [43] reported up to an 80% difference in the weight of A. domesticus fed a control diet containing 19.2% crude protein and 37.6% starch, and a red-clover-based diet. Collavo et al [42] found that an aromatic-arboreal diet is not optimal for A. domesticus, and its unbalanced nutritional value promoted cannibalism.…”
Section: Changes In the Larval Weight In Response To Dietmentioning
confidence: 99%
“…The crickets were known to be free of house cricket densovirus (Semberg et al, 2019). Prior to the study, all individuals were reared on a cereal-and rapeseed-based control feed (as in Vaga et al, 2020), prepared from commercial wheat flour, oat bran, wheat bran, rapeseed meal (ExPro 00SF, AAK AB, Malmö, Sweden), CaCO 3 and vitamin-mineral premix (Table 1), and cold-pressed into ⌀ 3 mm pellets. In the experiments, nymphs were randomly allocated to control and experimental groups within 24 hours of hatching.…”
Section: Crickets and Control Feedmentioning
confidence: 99%
“…Flowering common gypsophila was acquired from a local flower retailer and dried by the same procedure as the other plants. The common nettle product (Vaga et al, 2020) show that the crickets mature between 54-60 days. The experiment was therefore run for 62 days, at which time the first crickets on control feed had matured.…”
Section: Design and Management Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature was kept at 30±1 °C and relative humidity at 45-55%, with a 12 h lighting regime. Feed was provided ad libitum and consisted of a pelleted feed mixture of oat bran, wheat bran, wheat meal, rapeseed meal, limestone, and a premix of vitamins and minerals (Vaga et al, 2020). Water was given in plastic tubes (10 × Ø 1.2 cm) that were refilled every 5-10 days.…”
Section: Study Design and Materialsmentioning
confidence: 99%